Effect of hybrid cross-linkers on alginate microcapsules - Shi, Yichen. (2012)
Cell encapsulation is often used to transfer biological substances for therapeutic usage. The type of encapsulation material will affect the properties of the microcapsules and ultimately determine the effectiveness of the cell encapsulation process. In this project, the effect of different cross-linkers with different concentrations mixed together was investigated to ascertain its role in affecting the properties of alginate microcapsules. Based on the results, alginate microcapsules cross-linked with 0.05M barium chloride and 0.01M calcium chloride had the most ideal combination of good mechanical and diffusion properties.